PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA PEGAWAI DI KECAMATAN TENGGARONG KABUPATEN KUTAI KARTANEGARA - Muhamad Noor (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
Work performance of employees in an organization can be done through the government’s work environment and employee’s motivation. Improvement performance of the employees in the district of Kutai district Tenggarong can be done through an increase in optimal working and leverage the potential of its human resources by employees in order to creat organizational goals. Employee job performance is measured by the standardor criteria established organization.